Peran Financial Literacy Dalam Memediasi Financial Behavior Terhadap Financial Well-Being (Studi E-Wallet Dana) - Putri Lestari; Liana Mangifera (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The use of internet-based technology by the public continues to increase.Â  The most popular and effective server for using information systems is the internet. One form of technology that supports the stability of the ease of financial system services and increases economic efficiency is E-Wallet. DANA is a form of Indonesian digital wallet with non-cash transaction services that are more effective, transparent, and secure, coinciding with the development of E-wallet. DANA's design makes non-cash transactions and non-card wallets efficient. Interest in using a digital wallet in a person is influenced by various supporting factors, such as understanding financial literacy. Financial literacy is a measure of a person's capacity to handle their money wisely, which is reflected in their attitude, knowledge, and efficacy towards future financial well being. This research uses Smart-PLS data processing software with 114 respondents covering all people in Indonesia from various age groups, education, and income. The results of this study use the analysis of convergent validity test, reliability test, inner model test, and hypothesis testing.